PERLINDUNGAN HUKUM TERHADAP PEMEGANG SERTIFIKAT GANDA HAK MILIK ATAS TANAH DI INDONESIA - Satriani, satriani; Angraeni, Besse Sari (Institut Agama Islam Negeri Fattahul Muluk Papua, 2025)
Duplicate land certificates remain a significant issue as they frequently lead to land disputes that result in both material and immaterial losses for legitimate landowners. This study aims to examine the forms of legal protection available to owners affected by duplicate certificates. Using a normative legal research method, the study employs statutory and conceptual approaches supported by library research, and the findings are analyzed qualitatively. The results indicate that preventive legal protection involves several key measures, including Complete Systematic Land Registration (PTSL), land administration digitalization, strengthened internal supervision, capacity building for human resources, public education and socialization, and enhanced inter-agency coordination. In contrast, repressive legal protection focuses on dispute resolution through judicial processes, mediation, cancellation of duplicate certificates by the National Land Agency, compensation, and the enforcement of criminal sanctions when necessary. This research contributes theoretically to the discourse on legal protection within land administration, particularly in emphasizing the importance of the precautionary principle in certificate issuance. It also provides broader insights into how preventive and repressive legal mechanisms can effectively mitigate and resolve the ongoing challenges associated with duplicate land certificates.